Algebraic High-Level Nets as Weak Adhesive HLR Categories - Prange, Ulrike (Electronic Communications of the EASST, 2007)
Adhesive high-level replacement (HLR) systems have been recently introduced as a new categorical framework for double pushout transformations. Algebraic high-level nets combine algebraic specifications with Petri nets to allow the modelling of data, data flow and data changes within the net. In this paper, we show that algebraic high-level schemas and nets fit well into the context of weak adhesive HLR categories. This allows us to apply the developed theory also to algebraic high-level net transformations.